Google Maps Mashups with Google Mapplets - Young, Michael (Apress, 2012)
Well, that’s the end of your journey! I hope it has been enjoyable and you’ve learned a thing or two about geographic mashups along the way. It’s time now to take your mashup idea and apply the knowledge from this book to create a great new mashup—or, at least one to help me find a good happy-hour spot after work